Effectiveness of Monetary and Fiscal Policies Fiscal Policy Effectiveness on Inflation and Unemployment Reduction in South Kalimantan - Rahimah, Afiatur; Ananda Aulia Futra; Sepreika Mutiyara (UMBanjarmasin, 2023)
This research aims to analyze the effectiveness of monetary and fiscal policies in combating inflation and unemployment in South Kalimantan and Indonesia. Reliable primary data sources such as journals, the Central Bureau of Statistics, and the official website of Bank Indonesia were utilized in this qualitative analysis. Indonesia, as a developing country, faces economic stability challenges, and monetary and fiscal policies are crucial instruments used by the government and central bank to regulate inflation and the overall economy. South Kalimantan, despite its abundant natural resources, still encounters economic disparities between urban and rural areas and sustainable resource management issues. To address these challenges, the government implements monetary and fiscal policies to facilitate economic control. The central bank aims to balance the money supply and commodity availability to achieve controlled inflation, full employment, and smooth commodity distribution. Fiscal policy plays a vital role in regulating macroeconomic balance and influencing short-term economic demand while also impacting long-term economic capacity. The research findings indicate the effectiveness of these policies, demonstrated by the controlled inflation rate in 2022 due to their implementation by the government